2019
DOI: 10.3390/medicina55070337
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients Dietary Supplementation Advices for Celiac Patients on Long-Term Gluten-Free Diet with Good Compliance: A Review

Abstract: Background and objective: Often micronutrient deficiencies cannot be detected when patient is already following a long-term gluten-free diet with good compliance (LTGFDWGC). The aim of this narrative review is to evaluate the most recent literature that considers blood micronutrient deficiencies in LTGFDWGC subjects, in order to prepare dietary supplementation advice (DSA). Materials and methods: A research strategy was planned on PubMed by defining the following keywords: celiac disease, vitamin B12, iron, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 74 publications
(134 reference statements)
1
41
0
Order By: Relevance
“…Zinc deficiency affects about 50% of the celiac population and can affect protein synthesis leading to growth arrest [44]; thus, a zinc supplementation between 25-40 mg/day is recommended [60]. In the present study, Laminaria incorporation in pasta led to an increase of Zn from 4.8% to 6.3% RDA.…”
Section: Physicochemical Analysis Of Pastamentioning
confidence: 47%
See 2 more Smart Citations
“…Zinc deficiency affects about 50% of the celiac population and can affect protein synthesis leading to growth arrest [44]; thus, a zinc supplementation between 25-40 mg/day is recommended [60]. In the present study, Laminaria incorporation in pasta led to an increase of Zn from 4.8% to 6.3% RDA.…”
Section: Physicochemical Analysis Of Pastamentioning
confidence: 47%
“…As mentioned earlier, the most deficient minerals in a GF diet are Ca, Fe, Mg, and Zn. In a review, Rondanelli and co-workers [60] gathered suggestions and guidelines for supplementation with several minerals and Theethira et al [55] reported a reduction in calcium intake by about 76%-88% of patients adhering to a GF diet. Although Laminaria ochroleuca is a good source of Ca, the PP pasta only contributed to 1.9% of RDA for calcium, whereas Ca supplementation in the range of 1200-1500 mg/day is recommended.…”
Section: Physicochemical Analysis Of Pastamentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the clinical data, as it has been shown that patients on a GFD quite frequently suffer from micronutrient deficiencies. 25 A list of the 24 transporter genes affected by a GFD is presented in Table 1 .
Figure 5 Differential intestinal mucosal gene transcriptome between healthy control subjects and patients with celiac disease on a GFD.
…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest that the low expression of micronutrient transporters in the intestine explains described clinical micronutrient deficiencies (ie, iron, folate, B12, and various mineral and vitamin D deficiencies) in patients following a strict GFD. 25 , 34 , 35 , 36 The low expressions might be due to inadvertent gluten ingestion and indication of disease due to early mucosal injury. Complete elimination of dietary gluten seems impossible to maintain due to issues such as contamination of gluten-free foods, resulting in the ingestion of hundreds of milligrams of gluten per day in an attempted GFD.…”
Section: Discussionmentioning
confidence: 99%